Challenges to obtain halal certification among restaurants in northeast Thailand - Wannasupchue, Wannasiri; Mohamad, Siti Fatimah; Ishak, Farah Adibah Che; Ungku Zainal Abidin, Ungku Fatimah (Journal of Islamic marketing, 2023)
Purpose This study aims to explore the challenges of getting halal certification for restaurants in north-eastern Thailand. Design/methodology/approach Qualitative research approach was adopted to analyse the collected data. The research procedures and the interview questions were examined by the Ethics Committee for Research involving human subjects. In total, 10 restaurant owners were interviewed. Then, the interviews were transcribed, coded and grouped by using thematic analysis while the ATLAS ti. software was used for qualitative data analysis. The theme was finalised by three intercoder agreements. Findings The three challenges of obtaining halal certification among restaurants in north-eastern Thailand were the complicated process of getting halal certification, lack of restaurant owner commitment and high halal certification fee. Research limitations/implications The number of halal-certified restaurants are limited. Some restaurants refused to renew halal status but their information is still displayed on the halal authority website. Not only the number of restaurants but also time-limited. Further, a quantitative phase for prioritising was suggested. Practical implications The study can be beneficial to the halal authority and business holders as the two main stakeholders. The findings can be used to plan or develop halal strategies to increase the quality of halal restaurants. As informants mentioned common challenges, the findings could be applied as guidelines for a new business holder keen on halal implementation. Originality/value This research demonstrated the challenges of halal certification in a non-Muslim country, focussing on the north-eastern region of Thailand. The findings will add value to a potential business area. Therefore, the highlighted challenges could provide a novelty and be useful for Muslim marketing.